Metal-poor Type II Cepheids with Periods Less Than Three Days. (29th March 2018) - Kovtyukh, V.; Wallerstein, G.; Yegorova, I.; Andrievsky, S.; Korotin, S.; Saviane, I.; Belik, S.; Davis, C. E.; Farrell, E. M.
Abstract: We have analyzed 10 high-resolution spectra of Type II Cepheids with periods less than 3 days. We find that they clearly separate into two groups: those with near or slightly below solar metallicities, and those with [Fe/H] between −1.5 and −2.0. While the former are usually called BL Her stars, we suggest that the latter be called UY Eri stars. The UY Eri subclass appears to be similar to the short period variables in globular clusters of the Galactic Halo. Globular clusters with [Fe/H] > −1.0 almost never have Type II Cepheids.